Pattern of Dermatological Disease Encountered in a Hematology Ward: A Retrospective Analysis of Dermatology Consultation in a Hematology Ward in a Tertiary Care Center in Saudi Arabia - Amal Aboud Alasmari; Anadel Hassan Hakeem; Fatemah Saleh Bin Saleh; Shahad Yousef Alsaigh; Waleed Al Ajroush; Laila Ali Layqah; Salim Alawi Baharoon (Dermatology Research and Practice)
Introduction. Skin manifestations are common in hematology ward patients and can result from infection, malignancy, or chemotherapy. The purpose of this study was to identify the most common dermatological problems encountered in the adult hematology ward at King Abdullah Specialist Children Hospital (KASCH). Methods. This was retrospective chart review of 78 dermatology consultations based on electronic health records for all inpatients in hematology wards at KASCH between January 2016 and December 2017. Data were presented as mean ± SD for continuous variables. Results. During the study period, a total of 1391 inpatients were referred to the dermatology department. A total of 403 (29.0%) referrals were from the internal medicine department and 78 (5.6%) were from the hematology department, six of which were rejected by the dermatology department. Almost all requests for referral were managed on the same or the next day with only two requests after 3 days. There were more female (n = 40; 51.3%) than male patients (n = 38; 48.7%) and the average age ± SD was 40.7 ± 19.8 years. Patients were diagnosed with a diverse range of hematological diseases. A total of 27 (35.1%) patients were diagnosed with acute myeloid leukemia. Overall, 98 differential diagnoses were made by dermatologists with only 26 being confirmed by skin biopsy. Eight (30.8%) patients were diagnosed with graft versus host disease confirmed by skin biopsy. The diagnoses were changed in 12 cases after skin biopsy. Several types of dermatitis were diagnosed in hematology ward patients including stasis dermatitis and contact dermatitis. The source of infection was not specified in most cases and the infection was treated empirically. Conclusion. Various dermatological disorders and cutaneous manifestations are observed in hematology inpatients with morbilliform drug eruption and graft versus host disease being the most common.